Desain Dan Pembangunan Sistem Dan Aplikasi Point of Sale Pada Apotek Berbasis Website di Apotek Berjaya Farma - Rayhan, Muhammad Daffa; Yusup, Mohammad; Putra, Hardiansyah (Jurnal Mahajana Informasi, 2024)
This study aims to design and build a website-based Point of Sale (POS) system at Berjaya Farma Pharmacy to improve operational efficiency and sales management accuracy. This system is designed to automate various processes, such as transaction recording, real-time drug stock management, data input validation, and providing informative sales reports. This project uses the System Development Life Cycle (SDLC) development method with the stages of needs analysis, design, implementation, and testing. The implementation results show that the website-based POS system developed can improve sales process efficiency by reducing human error through automation of transaction recording and total price calculation. The drug stock management feature allows automatic stock data updates after transactions, thus helping to maintain inventory availability. In addition, the sales reports provided make it easier for pharmacy owners to analyze income and support strategic decision making. The data input validation feature also functions well, ensuring that data entered into the system is accurate and in accordance with the specified format.